PENERAPAN METODE BLENDED LEARNING UNTUK MENUMBUHKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA - EVA PURWANTI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This study aims to: 1). Growing Students' Interest in Learning through the Application of Blended Learning Methods in Indonesian Language Subjects in class IX of SMP Negeri 3 Singkawang. 2). The strategy carried out by the teacher in Fostering Student Interest in Learning through the Application of the Blended Learning Method in Indonesian Language Subjects in Class IX of SMP Negeri 3 Singkawang. The stages (phases) of learning with the Blended Learning Method are: 1). Determine teaching materials, 2) Determine the design of the blended learning used, and 3). Set the online learning format. and 4). Carry out a test of the design made. After the application of the Blended Learning Method to Grow Student Interest in Indonesian Language Subjects in class IX SMP Negeri 3 Singkawang was used in the classroom learning process, it was found that there was a change in the increase in student learning outcomes in the cognitive domain. When the evaluation was carried out, the results were much improved when compared to the learning outcomes in the speech text material in the previous Indonesian language subject with the lecture method alone. Of the 28 students, almost all 26 students or equivalent to 92.85% achieved the minimum learning mastery set for learning Indonesian while 2 students or equivalent to 7.14% obtained learning outcomes below the KKM, which is 70. ABSTRAKPenelitian ini bertujuan untuk: 1). Menumbuhkan Minat Belajar Siswa melalui Penerapan Metode Blended Learning Pada Mata Pelajaran Bahasa Indonesia di kelas IX SMP Negeri 3 Singkawang. 2). Strategi yang dilakukan oleh guru dalam Menumbuhkan Minat Belajar Siswa melalui Penerapan Metode Blended Learning Pada Mata Pelajaran Bahasa Indonesia di Kelas IX SMP Negeri 3 Singkawang. Adapun Tahapan-tahapan (Fase) pembelajaran dengan Metode Blended Learning yaitu: 1). Menetapkan materi ajar, 2) Menetapkan rancangan dari blended learning yang digunakan, dan 3). Menetapkan format pembelajaran online. Dan 4). Melakukan uji dari rancangan yang dibuat. Setelah Penerapan Metode Blended Learning untuk Menumbuhkan Minat Belajar siswa pada Mata Pelajaran Bahasa Indonesia di kelas IX SMP Negeri 3 Singkawang digunakan dalam proses pembelajaran di kelas, diketahui terjadi perubahan dalam peningkatan pemerolehan hasil belajar siswa pada ranah kognitif. Ketika dilakukan evaluasi diperoleh hasil yang jauh meningkat jika dibandingkan dengan hasil belajar pada materi Teks pidato pada mata pelajaran Bahasa Indonesia sebelumnya dengan metode ceramah saja. Dari 28 siswa hampir seluruh siswa 26 orang atau setara dengan 92,85% mencapai ketuntasan belajar minimum yang ditetapkan pada pembelajaran Bahasa Indonesia sedangkan 2 orang atau setara dengan 7,14% memperoleh hasil belajar di bawah KKM yaitu 70.